METHODS FOR IMPROVING REPRODUCTIVE AND PRODUCTIVE ABILITIES OF QUEEN BEE IN THE SOUTH OF KAZAKHSTAN - Shimelkova, R. Zh.; Aldiyarova, A. K.; Demidova, I. V.; Dosbolat, Zh. B.; Nuralieva, U. A. (ЗКАТУ им. Жангир хана, 2023)
A study was carried out on the development of breeding methods, improving the productive and reproductive qualities of queen bees. The intake and size of fed queen cells, the dependence of the mass of queens on the mass of the host family, the effect of honey-bee-bread feeding of host families on the volume of queen cells and the weight of queens, as well as various methods of replanting into full-fledged families were studied. It has been established that with less upbringing of queen cells, the nurse bees intensively fill the bowls with royal jelly, while the larvae that receive a large amount of food increase in size and, when they emerge, the weight of the barren queen increases. The quality of the queens is largely determined by the conditio ns of their cultivation and feeding in the nurse colonies, while it was determined that the highest live weight of the uterus is observed in strong nurse colonies with a composition of bees of different ages. The stronger the foster family was, the higher the quality of the queens. The most effective method of replanting fetal queens was the replanting of fetal queens in a cell, which guarantees a successful 85% intake. When using various methods of replanting fetal queens in full-fledged colonies, it was shown that it is much easier to plant a new queen in small colonies that are in a state of intensive growth than in strong ones, while young nonflying bees practically do not show aggressiveness towards the replanted queen.
Shimelkova , R. Zh. METHODS FOR IMPROVING REPRODUCTIVE AND PRODUCTIVE ABILITIES OF QUEEN BEE IN THE SOUTH OF KAZAKHSTAN / R. Zh. Shimelkova , A. K. Aldiyarova, I. V. Demidova , Zh. B. Dosbolat, U. A. Nuralieva. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2023. - № 3-2 (72). Ч. ІІ. - Р. 222-229. - ISSN 2305-9397
Keywords: beekeeping; queen bee; hatching; mother liquor; egg tubes; live weight; научный журнал; зкату